2008
DOI: 10.2459/jcm.0b013e32820588dd
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting coronary flow reserve impairment in patients evaluated for chest pain: An ultrasound study

Abstract: In patients with acute chest pain, the occurrence of multiple cardiovascular risk factors adversely affected CFR in an additive manner, in absence of significant angiographic stenosis. Diabetes mellitus was a powerful coronary risk factor decreasing CFR both in patients with or without significant LAD disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…This prevalence is similar to other studies investigating CMD in this patient population [5, 31, 48, 49]. Impaired CMD was associated with hypertension and higher resting heart rate which is similar to findings from other studies [3, 31, 50, 51]. …”
Section: Discussionsupporting
confidence: 91%
“…This prevalence is similar to other studies investigating CMD in this patient population [5, 31, 48, 49]. Impaired CMD was associated with hypertension and higher resting heart rate which is similar to findings from other studies [3, 31, 50, 51]. …”
Section: Discussionsupporting
confidence: 91%
“…The nonendothelial aspect of the coronary microcirculation can be determined by assessment of the coronary flow velocity reserve (CFVR) . Impaired CFVR is associated with cardiovascular risk factors and is a robust predictor of adverse prognosis in various patient populations …”
Section: Introductionmentioning
confidence: 99%
“…3 The nonendothelial aspect of the coronary microcirculation can be determined by assessment of the coronary flow velocity reserve (CFVR). 4 Impaired CFVR is associated with cardiovascular risk factors [5][6][7][8] and is a robust predictor of adverse prognosis in various patient populations. 5,[9][10][11][12] It has been suggested that CMD can cause left ventricular (LV) diastolic dysfunction and contribute to development of heart failure with preserved ejection fraction but limited data exist in support of this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…66 Aging is associated with arterial remodeling 67 and has been shown to be a risk factor for CMD in numerous studies. 6,20,68, 69 In patients with hypertension and reduced CFR, arteriolar remodeling, including increased medial wall thickness and periarteriolar fibrosis, are seen on biopsy. 70,71 Low-density lipoprotein (LDL)-cholesterol level has been found to inversely correlate with CFR.…”
Section: Risk Factorsmentioning
confidence: 99%